Deformation mechanisms and dynamic recrystallisation of Zr alloy with different initial textures compressed at 700°C. (July 2014) - Luan, B. F.; Li, X. Y.; Zhang, M.; Chapuis, Adrien; Liu, Q.
Abstract : The hot deformation behaviour depends on the initial texture. In this study a hot rolled Zr alloy plate with a bimodal basal texture has been compressed at 700°C along two directions to study the effect of initial texture on deformation mechanisms and dynamic recrystallisation (DRX). Four strain levels (10, 20, 30 and 45%) of uniaxial compression were analysed. Microstructures and textures of deformed specimens were characterized and compared by electron backscatter diffraction (EBSD). At 10% strain, twins were observed in the two textures, but {10–12} tensile twins predominate in the sample with the bimodal basal texture normal to the compression direction. As the compression strain accumulates to 20%, DRX is also affected by the initial texture. When the c-axis is close to the compression axis (CA), extensive DRX process was observed. If the c-axis is perpendicular to the CA, DRX was obviously retarded. Due to the initiation of twinning, the stored energy accumulated by dislocations was relatively low. After 45% compression, the two specimens developed the same bimodal basal texture with the c-axis of most grains rotated toward CA.